Analisis Faktor-Faktor Yang Mempengaruhi Ketimpangan Pendapatan Di Provinsi Jawa Timur (Tahun 2011-2015) - Wicaksani, Rossy Agustin, Muh. Arif, SE., MEc. Dev (2017)
Inequality of income or the income gap between high-income groups and low-income groups is a major problem that is commonly faced by developing countries, including Indonesia. The aim of this study was to analyze the factors unruk that mepengaruhi inequality in the province of East Java in 2011-2015. This study uses four independent variables namely IPM, economic growth, employment and population. The data used in this research is secondary data analysis method used in this research is the analysis of panel data regression. Results obtained from panel data regression analysis that Random Effects Model (REM) is a panel data regression model is most appropriate. Based on test validity or the effect of the t test, that the variables that significantly influence income inequality in the province of East Java in 2011-2015 is simply the HDI variable with a positive influence.